2008
DOI: 10.1177/0734242x07087977
|View full text |Cite
|
Sign up to set email alerts
|

Biotic systems to mitigate landfill methane emissions

Abstract: Landfill gases produced during biological degradation of buried organic wastes include methane, which when released to the atmosphere, can contribute to global climate change. Increasing use of gas collection systems has reduced the risk of escaping methane emissions entering the atmosphere, but gas capture is not 100% efficient, and further, there are still many instances when gas collection systems are not used. Biotic methane mitigation systems exploit the propensity of some naturally occurring bacteria to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
107
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(118 citation statements)
references
References 94 publications
2
107
0
9
Order By: Relevance
“…High-affinity methanotrophic bacteria exist in soils temporarily exposed to CH 4 concentration. Low-affinity methanotrophic bacteria exhibit a high oxidation capacity, with CH 4 levels in the range of 0.8-66 μmol L -1 (Huber- Humer et al, 2008). Low-affinity methanotrophic bacteria are more prevalent in landfill cover soils than are the high-affinity variant (Kightley et al, 1995).…”
Section: Methane Oxidation Bacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…High-affinity methanotrophic bacteria exist in soils temporarily exposed to CH 4 concentration. Low-affinity methanotrophic bacteria exhibit a high oxidation capacity, with CH 4 levels in the range of 0.8-66 μmol L -1 (Huber- Humer et al, 2008). Low-affinity methanotrophic bacteria are more prevalent in landfill cover soils than are the high-affinity variant (Kightley et al, 1995).…”
Section: Methane Oxidation Bacteriamentioning
confidence: 99%
“…For simplicity, previous studies have reported that the CH 4 oxidation process in landfill cover soils is accomplished by methanotrophic bacteria (Abushammala et al, 2012;Huber-Humer et al, 2008;Albanna et al, 2007;Stern et al, 2007;Kettunen et al, 2006). Methanotrophic bacteria (Fig.…”
Section: Methane Oxidation Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…When we speak today of going green, we generally refer to something broader than global warming. The term today includes efforts to conserve our natural resources, reduce our contributions to landfills, and reduce pollution generally [7][8][9].…”
Section: Introductionmentioning
confidence: 99%